THE INFLUENCE OF PROFITABILITY, LEVERAGE, AND CAPITAL INTENSITY ON INDICATIONS OF TAX AVOIDANCE - hadiwibowo, imam; Azis, Mohammad Taufik; Aprilia, Restia (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
Taxes are the biggest contribution to the growth of a country, including Indonesia. On the other hand, many taxpayers consider taxes a burden that can reduce income, so many taxpayers still try to carry out indications of tax avoidance. The aim of this research is to determine the effect of profitability, leverage, and capital intensity on indications of tax avoidance. In this research, indications of tax avoidance can be measured using CTTOR. Research carried out by the author using a purposive sampling method obtained 67 sample companies in the property and real estate industries listed on the Indonesia Stock Exchange for the 2020–2022 period. The analytical method used is multiple linear regression analysis using SPSS V24. In this research, the results obtained partially show that profitability has a negative effect on indications of tax avoidance and leverage has a positive effect on indications of tax avoidance. while capital intensity has no effect on tax avoidance. simultaneously shows that profitability, leverage, and capital intensity influence indications of tax avoidance.